Alloy Microstructure Dictates Corrosion Modes in THA Modular Junctions. Issue 12 (December 2017) - Pourzal, Robin; Hall, Deborah J.; Ehrich, Jonas; McCarthy, Stephanie M.; Mathew, Mathew T.; Jacobs, Joshua J.; Urban, Robert M.
Abstract : Background : Adverse local tissue reactions (ALTRs) triggered by corrosion products from modular taper junctions are a known cause of premature THA failure. CoCrMo devices are of particular concern because cobalt ions and chromium‐orthophosphates were shown to be linked to ALTRs, even in metal‐on‐polyethylene THAs. The most common categories of CoCrMo alloy are cast and wrought alloy, which exhibit fundamental microstructural differences in terms of grain size and hard phases. The impact of implant alloy microstructure on the occurring modes of corrosion and subsequent metal ion release is not well understood. Questions/purposes : The purpose of this study was to determine whether (1) the microstructure of cast CoCrMo alloy varies broadly between manufacturers and can dictate specific corrosion modes; and whether (2) the microstructure of wrought CoCrMo alloy is more consistent between manufacturers and has low implications on the alloy's corrosion behavior. Methods : The alloy microstructure of four femoral‐stem and three femoral‐head designs from four manufacturers was metallographically and electrochemically characterized. Three stem designs were made from cast alloy; all three head designs and one stem design were made from wrought alloy. Alloy samples were sectioned from retrieved components and then polished and etched to visualize grain structure and hard phases such as carbides (eg, M23 C6 ) or intermetallic phases (eg, σ phase). Potentiodynamic polarization (PDP) tests were conducted to determine the corrosion potential (Ecorr ), corrosion current density (Icorr ), and pitting potential (Epit ) for each alloy. Four devices were tested within each group, and each measurement was repeated three times to ensure repeatable results. Differences in PDP metrics between manufacturers and between alloys with different hard phase contents were compared using one‐way analysis of variance and independent‐sample t‐tests. Microstructural features such as twin boundaries and slip bands as well as corrosion damage features were viewed and qualitatively assessed in a scanning electron microscope. Results : We found broad variability in implant alloy microstructure for both cast and wrought alloy between manufacturers, but also within the same implant design. In cast alloys, there was no difference in PDP metrics between manufacturers. However, coarse hard phases and clusters of hard phases (mainly intermetallic phases) were associated with severe phase boundary corrosion and pitting corrosion. Furthermore, cast alloys with hard phases had a lower Epit than those without (0.46 V, SD 0.042; 0.53 V, SD 0.03, respectively; p = 0.015). Wrought alloys exhibited either no hard phases or numerous carbides (M23 C6 ). However, the corrosion behavior was mainly affected by lattice defects and banded structures indicative of segregations that appear to be introduced during bar stock manufacturing. Alloys with banding had a lower Ecorr (p = 0.008) and higher Icorr (p = 0.028) than alloys without banding (−0.76 V, SD 0.003; −0.73 V, SD 0.009; and 1.14 × 10 −4 mA/cm 2, SD 1.47 × 10 −5 ; 5.2 × 10 −5 mA/cm 2, SD 2.57 × 10 −5, respectively). Alloys with carbides had a slightly higher Ecorr (p = 0.046) than those without (−0.755 V, SD 0.005; −0.761 V, SD 0.004); however, alloys with carbides exhibited more severe corrosion damage as a result of phase boundary corrosion, hard phase detachment, and subsequent local crevice corrosion. Conclusions : The observed variability in CoCrMo alloy microstructure of both cast and wrought components in this study appears to be an important issue to address, perhaps through better standards, to minimize in vivo corrosion. The finding of the banded structures within wrought alloys is especially concerning because it unfavorably influences the corrosion behavior independent of the manufacturer. The findings suggest that a homogeneous alloy microstructure with a minimal hard phase fraction exhibits more favorable corrosion behavior within the in vivo environment of modular taper junctions, thus lowering metal ion release and subsequently the risk of ALTRs to corrosion products. Also, the question arises if hard phases fulfill a useful purpose in metal‐on‐polyethylene bearings, because they may come with a higher risk of phase boundary corrosion and pitting corrosion and the benefit they provide by adding strength is not needed (unlike in metal‐on‐metal bearings). Clinical Relevance : Implant failure resulting from corrosion processes within modular junctions is a major concern in THA. Our results suggest that implant alloy microstructure is not sufficiently standardized and may also dictate specific corrosion modes and subsequent metal ion release.